Descriptive Statistics using LibreOffice Calc software: experiment with a virtual cube (Research, Society and Development, 2021)
With the advent of the computer, several alternatives in the process of teaching and learning mathematics have been discussed in several congresses of education, science and technology. Teacher and students interact fully in the search for solutions to this educational transformation in order to generate models that value critical, creative and innovative thinking. The use of Information and Communication Technologies - ICTs in the school environment has caused drastic changes in the way of teaching and the way of learning mathematics. This article aimed to present a suggestion of a motivational class for elementary school students, using descriptive statistical measures in the LibreOffice Calc software. Some questions will be presented that may question the true efficiency of a motivational class in Statistics in Basic Education using the LibreOffice Calc Software. Educational proposals such as this one are expected to be fundamental to bring the traditional school closer to the technological world.